COMMUNITY EMPOWERMENT THROUGH TRAINING ON THE MANAGEMENT OF VILLAGE-OWNED ENTERPRISES (BUMDES) IN UJAN MAS DISTRICT, KEPAHIANG REGENCY - Hatta, Madani; Baihaqi, Baihaqi; Fachruzzaman, Fachruzzaman; Aprida, Cici; Darma, Fahreza Novrian; Maulana, Lucky Hikmat (LPPM Univ. Ibn Khaldun Bogor, 2025)
This community service activity aims to increase the capacity and competence of the management of Village-Owned Enterprises (BUMDes) in Ujan Mas District, Kepahiang Regency, in terms of institutional governance, financial management, and business development based on local potential. The training was carried out through lectures, interactive discussions, and hands-on practice involving village officials, BUMDes administrators, and community leaders. The results of the activity showed an increase in participants' understanding of the basic concept of the establishment and management of BUMDes that is accountable and sustainable. In addition, participants were also able to prepare a village business development plan according to their needs and potential. This activity is expected to be the first step in encouraging village economic independence through optimizing the role of BUMDes as a driver of the local economy.